Formulating Contextual Building Regulations for Hill Towns of India: The Case of Shimla. (1st January 2018) - Kumar, Ashwani; Garg, Pushplata
Abstract: Hill towns of India are best known for their salubrious climate, scenic beauty, picturesque setting and healthy living environment. Hill towns have been experiencing high pressure for development for the last three decades and as a result, are facing numerous problems related to new development that is contextually inappropriate and leads to deteriorated living conditions and poor environmental quality. Most of the issues of existing development are due to contextually inappropriate building regulations, which are formulated without consideration of the geoenvironmental and developmental context of environmentally sensitive hill towns. Moreover, no scientific and systematic approach is followed for the formulation of regulations. A new approach based on various intrinsic characteristics and factors is required for formulation of building regulations in the particular context to hill towns of India. The relevant issues related to building regulations are highlighted in this paper along with the identification of a more suitable building regulatory system for the specific context of hill towns. The article suggests a new approach for the formulation of building regulations for hill towns, based on various intrinsic characteristics and different factors, which are crucial for contextual development in hill towns.